INVESTIGATION OF THE STRENGTH PROPERTIES OF FROZEN SOILS. FISCAL YEAR 1952. APPENDIX A: INVESTIGATIONAL DATA. VOLUME 2. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1953)
The report contains tabular data describing the mechanical properties of various types of frozen soils.